Resentment's virtue : Jean Améry and the refusal to forgive - Brudholm, Thomas, 1969- (Politics, history, and social change., 2008)
Arguing beyond hasty dichotomies and unexamined moral assumptions, Resentment's Virtue offers a more nuanced approach to an understanding of the reasons why survivors of mass atrocities sometimes harbour resentment and refuse to forgive. Building on a close examination of the writings of Holocaust-survivor Jean Amry, Brudholm argues that the preservation of resentment or the resistance to calls for forgiveness can be the reflex of a moral protest and ambition that might be as permissible, humane or honourable as the willingness to forgive.